Intraoperative Local Administration of Platelet-Rich Plasma (PRP) during Neurolysis Surgery for the Treatment of Digital Nerve Crush Injury - Akira Ikumi; Yuki Hara; Eriko Okano; Sho Kohyama; Norihito Arai; Yu Taniguchi; Hisashi Sugaya; Tomokazu Yoshioka; Akihiro Kanamori; Masashi Yamazaki (Case Reports in Orthopedics)
The digital nerves are important for normal hand function. In addition to conventional therapies such as neurolysis, direct repair, and auto/allografts, new treatments administering growth factors and cells for promoting nerve regeneration exist. Platelet-rich plasma (PRP), an autologous product with proven therapeutic effects for musculoskeletal disorders, is a new treatment option for peripheral nerve injury. We hypothesized that PRP could stimulate healing of digital nerve injuries. In the current case report, intraoperative local administration of PRP was performed during neurolysis surgery for a healthy 28-year-old woman with digital nerve crush injury. Five weeks postinjury, surgery was performed due to severe uncontrollable neuropathic pain and no sensory nerve action potential derivation of the index finger. Therapeutic effects were assessed by physical examination, visual analog scale for pain, and nerve conduction study. Postoperatively, early neuropathic pain relief and good functional recovery were obtained with no PRP-related adverse events. This case report demonstrates the therapeutic potential of intraoperative PRP to enhance the healing process of nerve crush injury in the acute phase and to decrease the neuropathic pain, thus enhancing healing of peripheral nerve crush injury.